Pengembangan Sistem Informasi Ketinggian Air dan Monitoring Kadar pH dan Suhu Air Pada Tambak Berbasis IoT - Hariyanto, Agus; Naufal Prayitno, Muhammad; Lewi, Lewi; Kadir Muhammad, Abdul (Politeknik Negeri Ujung Pandang, 2025)
Ponds are one of the most popular cultivation methods in Indonesia. The Ministry of Maritime Affairs and Fisheries (KKP) recorded an increase in the value of fishery exports of 10.66% in the January – November 2022 period compared to the previous year. To increase fishery harvest yields requires the use of technology, one of the problems is regarding water quality, a decrease in water quality can disrupt fishery harvest results. The aim of this research is to create an Android application for monitoring water level, pH and temperature which was developed to help fish farmers monitor the condition of their ponds. The research method used is by conducting literature studies and interviews, then developing previous research by adding a pH sensor, GSM module, and updating the application display as well as optimizing PI control for water level control, then taking data from the sensor reading results compared with existing measuring instruments. tested to determine the level of accuracy and the information system data is taken on the average time required to send data to the application. The research results obtained are that the information system and water level monitoring for a prototype robot to control water levels in ponds has been developed by adding a GSM module as an alternative. replacement for the Wifi network with an average data transmission time of 3.6 seconds and implementation of PI control in the water level control system. Detecting water pH levels on a prototype robot that controls water levels in ponds has been successfully created and implemented with an average reading error of 2.15%. The water temperature reading on the prototype robot that controls water levels in ponds has been successfully optimized so that it has an average temperature reading error of 1.69%.